Characterization of wild fish diet and trophic guild in a protected area - Ramos, Julia Kaori Kuriyama [UNESP] (2022)
Aim: We characterize the diet and trophic guild to the fish community in a protected area to contribute information about the trophic ecology. Methods: The collection was carried out at three sampling points, in 2017 and 2018, with the help of gill nets. The collected specimens were euthanized in a 0.5% benzocaine solution. In the laboratory, all specimens’ stomachs were removed, fixed in a 4% formalin solution, and preserved in 70% alcohol. Stomach contents were examined, and the food items were identified to the lowest possible taxonomic level. Food items were quantified according to the volumetric method. The characterization of the diet was presented through the percentage volume of each food item consumed. To determination of the trophic guild of each species, the predominance of a type of food resource (> 51% of the total volume) in the population’s diet was considered. Results: The species’ diets were distributed in 16 food items (predominance of decapods, fish fragments, terrestrial insects, and aquatic plants), and four trophic guilds were observed (carcinophage, piscivore, terrestrial insectivore, and herbivore). Furthermore, there was the occurrence of microplastic in the diet of three species. Conclusions: the fish community evaluated here demonstrates the wide range of resources that can make up the fish diet and demonstrates the different trophic guilds that can be observed in a protected area. As it is a conservation unit, knowing the diet and trophic guilds that make up the fish community can contribute to understanding the dynamics of food chains, the structure of the community, and the functioning of the ecosystem. Thus, this work can contribute information about the biology of the species evaluated for future work and conservation programs.